Welfare Implications of Supplier Encroachment with Consumer Shopping Costs - Stéphane Caprice; Shiva Shekhar (CESifo GmbH, 2025)
In this paper, we study supplier encroachment in competition with multi-product retailers and its effects on retail profits under endogenous consumer shopping behavior. We find that supplier encroachment (weakly) increases both supplier and retailer profits, as the retailer benefits from better consumer segmentation and price discrimination despite (weakly) higher wholesale prices. The effect of encroachment on consumers is more nuanced: when the competitive product's value is high, consumers benefit. Instead, when the value of the competitive product is low, consumers buying exclusively from the multi-product retailer are worse off while consumers who mix and match across stores are better off. Overall, supplier encroachment can improve market outcomes if the value of the supplier's product offering is sufficiently high.
Keywords: L13; L22; L42; L81; 330; supplier encroachment; vertical contracting; downstream competition; consumer shopping costs.